Predicting BPD: Lessons Learned From the Airway Microbiome of Preterm Infants - Gentle, Samuel J.; Lal, Charitharth Vivek (Frontiers in Pediatrics, 2020)
Bronchopulmonary dysplasia (BPD) is the chronic lung disease of prematurity with an operational definition, various different clinical phenotypes and a complex, multifactorial etiology. Newer unbiased systems biology approaches have identified various ‘omic’ factors associated with the pathogenesis and prediction of BPD. Recent microbi'omic’ studies have discovered that airways of newborns harbor a low biomass but distinct microbiome signature as early as at the time of birth. This early airway microbiome may serve to prime the host immune system, and may play a role in modulating the infant’s future susceptibility to severe BPD development. Temporal changes are observed in airway microbiome of preterm infants from birth to the diagnosis of BPD, with an overall decrease in bacterial diversity, and development of a relative dysbiosis marked by increased Gammaproteobacteria and decreased Lactobacilli abundance. This review will summarize previous investigations of the airway microbiome in preterm infants, appraise the utility of using the airway microbiome to predict BPD development, discuss possible molecular mechanisms involved, and speculate on future microbiome mediated therapeutics for BPD.